A Cross sectional study to assess the DMFT, Oral Health related behavior and practice among the selected school of old Dhaka city, Bangladesh (Update Dental College Journal, 2021)
This cross-sectional type of descriptive study was conducted to assess the DMFT, oral health related behavior and practice in Rajer Deuri Government primary school in old Dhaka, Bangladesh.About 158 school children were selected by the purposive type of non-probability sampling technique. Face to face interview with questionnaire followed byChecklist. Out of 158 students, 78 (49.4%) were 12-14 years whereas maximum 80 (50.6%) of them were male and 78 (49.4%) were female. Againmajority students fathers were secondary level 34.2 and mothers were primary level passed 41.1%. Maximum family income belongs to 81 (51.3%) which is ranges from 10000-20000 Tk.Majority 89(56.3%) of the respondents never visited dentist. Again, maximum uses tooth paste with brushes 155(98.1%) and also majority 64(40.5%). use a new tooth brush as long as last Maximum make a visit to the dentist about 62(39.2%) on having toothache. Moreover,though128 (81.0%) agree that consumption of sugar in between meals causes dental caries but 130(82.3%) did not know about fluoride. Again, 64(40.5%) respondents knows not cleaning their teeth may cause tooth decay. In addition, 89(56.3%) students don’t know aboutgum bleeding while 52(32.9%). About 116 (73.4%) of the students didn’t know how to protect their gumMoreover, 118(74.7%) & 135(85.4%) of the respondents don’t know about dental plaque & calculus but 136(86.1%) & 98(62.0%) knows sweet food & soft drinks may affect dental health. Again, maximum 100(63.3%) respondents think that the health of mouth impact on the health of body as well as their treatment is also important. About130 (82.3%) of the respondents thinks that brushing teeth may prevent tooth decay while maximum 134 (84.8%) of the respondents did not know using fluoride strength their teeth. Maximum, 122 (77.2%) & 134(84.8%) did not know using toothbrush& floss help them preventing periodontal disease. Though 79(50.0%) of the respondents mentioned that using toothbrush & flossing is the best method for prevention of tooth decay. About 89(56.3%) of the respondents brush their teeth more than 2 minutes. Maximum 83(52.5%) & 129 (81.6%) of them did not know about the number of their permanent & deciduous tooth. About 136(86.1%) of the students did not know eruption time of 1st permanent molar. Finally, 118 (74.7%) out of 158 get knowledge about oral health from their family.There is a significant association between fathers & mothers education with knowledge which resembles (P value is 0.001). Again, therewas a statistical significant association between cleaning in between teeth and their knowledge (P value is 0.012) and also on having toothache maximum did not visit to the dentist where (P value is